Bis{5-methoxy-2-[(2-morpholinoethyl)iminomethyl-κN]phenolato-κO1}nickel(II) - Nooraziah Mohd Lair; Hapipah Mohd Ali; Seik Weng Ng (Acta Crystallographica Section E, 2009)
The asymmetric unit of the crystal structure of the title compound, [Ni(C14H19N2O3)2], contains two independent NiII complex molecules, with the metal atoms each located on a center of inversion. Each metal atom is chelated by two Schiff base anions in a distorted square-planar coordination environment.